Cobalt-free SrFe0.9Ti0.1O3−δ as a high-performance electrode material for oxygen reduction reaction on doped ceria electrolyte with favorable CO2 tolerance - Yang, G.; Su, Chao; Chen, Y.; Dong, F.; Tade, Moses; Shao, Zongping (Elsevier Ltd, 2014)
A cobalt-free titanium-doped SrFeO3−δ perovskite with a nominal composition of SrFe0.9Ti0.1O3−δ (SFT) is exploited as an alternative electrode for solid oxide fuel cells (SOFCs). Special attention is given to the effects of CO2 on the oxygen reduction reaction (ORR) performance and properties of the oxide. For this investigation, XRD, HR-TEM, FT-IR, 4-probe DC conductivity, EIS and SEM are used. Although no bulk carbonate is formed, even under a pure CO2 atmosphere, the chemical adsorption of CO2 only appears over the SFT surface, which suggests a weak effect of CO2 on the structure of SFT. The EIS tests demonstrate that such CO2 adsorption does have a modest and detrimental effect on the ORR over the SFT electrode. However, the electrochemical performance can be easily recovered after removing of CO2. Thus, SrFe0.9Ti0.1O3−δ is a promising cathode material for practical SOFCs due to its high activity, high CO2 tolerance, and low cost.